STRATEGIC FUNCTIONS OF AND PROSPECTS FOR THE FOREIGN MILITARY PRESENCE IN CENTRAL ASIA - BOBOKULOV, Inomjon (CENTRAL ASIA AND THE CAUCASUS, 2012)
At all times, armed forces have dominated and still dominate the development of statehood: they protect the fundamental interests of states—sovereignty and territorial integrity—and their capabilities are widely used as an effective instrument for implementing foreign policy, determining, along with the economy and ideology, a state’s impact on world politics. Armed forces have retained their adequacy amid the current globalization trends when traditional (military) threats are retreating, states’ security interests are growing increasingly interdependent, and the principle of their in-divisibility is being widely recognized, while the world has acquired alternative forces and means to ensure security, etc. Today, however, military spending is constantly climbing, while the “responsibility zone”/ “geography of functioning "of armed forces outside their state borders is widening. The national interests of the sovereign entities of world politics suggested by the very nature of international relations and security threats presuppose a wider network of military bases overseas. The foreign military presence is directly connected with events and processes that reverberate across the world and which, at different periods in human history, have been the driving force behind progress. In the past, in the 17th-20th centuries, military bases in foreign countries were set up by colonial powers or by the great powers locked in the ideologically driven Cold War.1 Early in the 21st century, this trend survived because of transnational threats (mainly from inter-national terrorism and the proliferation of WMD), as well as due to the struggle for strategic resources. Here I will analyze the foreign military bases that appeared in Central Asia along with the “global war against terrorism” and the prospects for new military facilities in conjunction with the interests of the Central Asian states.